VD_FINDINFO HC / 2009 / 275 vom 25. August 2009 - VD Tribunal cantonal (2009)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, DÉPENS, RESTITUTIONEN GÉNÉRAL | 518 CPC, 94 al. 1 CPC, 94 al. 4 CPC, 94 CPC, 21 al. 1 LPEBL, 21 LPEBL